Moldova : A Story of Upward Economic Mobility - Davalos, Maria E.; Meyer, Moritz (World Bank Group, Washington, DC, 2015)
During the early 2000s, Moldova experienced strong economic growth and poverty and inequality reductions. This paper aims at uncovering the patterns behind these poverty trends by looking at economic mobility and its associated factors in Moldova. The findings build on the synthetic panel approach and allow for a non-anonymous view of the process of poverty reduction. The data used for this country study on Moldova come from the Household Budget Survey, which is conducted on a yearly basis. The paper presents transition matrices to look at the patterns of economic mobility across selected consumption thresholds, as well as descriptive statistics and a linear probability model aimed at identifying correlates of economic mobility. The findings show that the observed poverty reductions happened with little churning, and highlight the importance of education and employment on upward economic mobility in Moldova in the 2000s, as well as the role of public and private transfers.